Staphylococcus lugdunensis infective endocarditis: description of 10 cases and analysis of native valve, prosthetic valve, and pacemaker lead endocarditis clinical profiles. (18th January 2005) - Anguera, I; Del Río, A; Miró, J M; Matínez-Lacasa, X; Marco, F; Gumá, J R; Quaglio, G; Claramonte, X; Moreno, A; Mestres, C A; Mauri, E; Azqueta, M; et al.
Abstract : Objective: To evaluate the incidence and the clinical and echocardiographic features of infective endocarditis (IE) caused by Staphylococcus lugdunensis and to identify the prognostic factors of surgery and mortality in this disease. Design: Prospective cohort study. Setting: Study at two centres (a tertiary care centre and a community hospital). Patients: 10 patients with IE caused by S lugdunensis in 912 consecutive patients with IE between 1990 and 2003. Methods: Prospective study of consecutive patients carried out by the multidisciplinary team for diagnosis and treatment of IE from the study institutions. English, French, and Spanish literature was searched by computer under the terms "endocarditis" and " Staphylococcus lugdunensis " published between 1989 and December 2003. Main outcome measures: Patient characteristics, echocardiographic findings, required surgery, and prognostic factors of mortality in left sided cases of IE. Results: 10 cases of IE caused by S lugdunensis were identified at our institutions, representing 0.8% (four of 467), 1.5% (two of 135), and 7.8% (four of 51) of cases of native valve, prosthetic valve, and pacemaker lead endocarditis in the non-drug misusers. Native valve IE was present in four patients (two aortic, one mitral, and one pulmonary), prosthetic valve aortic IE in two patients, and pacemaker lead IE in the other four patients. All patients with left sided IE had serious complications (heart failure, periannular abscess formation, or shock) requiring surgery in 60% (three of five patients) of cases with an overall mortality rate of 80% (four of five patients). All patients with pacemaker IE underwent combined medical treatment and surgery, and mortality was 25% (one patient). In total 59 cases of IE caused by S lugdunensis were identified in a review of the literature. The combined analysis of these 69 cases showed that native valve IE (53 patients, 77%) is characterised by mitral valve involvement and frequent complications such as heart failure, abscess formation, and embolism. Surgery was needed in 51% of cases and mortality was 42%. Prosthetic valve endocarditis (nine of 60, 13%) predominated in the aortic position and was associated with abscess formation, required surgery, and high mortality (78%). Pacemaker lead IE (seven of 69, 10%) is associated with a better prognosis when antibiotic treatment is combined with surgery. Conclusions: S lugdunensis IE is an uncommon cause of IE, involving mainly native left sided valves, and it is characterised by an aggressive clinical course. Mortality in left sided native valve IE is high but the prognosis has improved in recent years. Surgery has improved survival in left sided IE and, therefore, early surgery should always be considered. Prosthetic valve S lugdunensis IE carries an ominous prognosis.